Effect of Laser Wavelength on AZO Surface Texturing by Direct Laser Processing / Patterning for Thin-Film Silicon Solar Cells Applications. (9th January 2018) - Demircioglu, Zeynep; Nasser, Hisham; Balog, Robert S.; Turan, Rasit
ABSTRACT: Surface texturing of transparent conductive oxides is crucial to improve the fraction of incident light trapped in the absorber layer of thin film silicon based solar cells to improve the device performance. In this work, we fabricate and compare periodic, overlapping, and random surface textures and patterns on aluminium doped zinc oxide (AZO) using direct laser processing. The effects of the used laser wavelength, laser operating frequency, and pulse periodicity on the structural, morphological, and optical response of the AZO films were investigated. By optimizing the laser parameters and the associated process conditions, a drastic increase up to 60% in the transmittance haze over the entire solar was achieved.